2015
DOI: 10.1177/0394632015598849
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine induces apoptosis and autophagy in human lung cancer cells through inhibition of PI3K/Akt/mTOR pathway

Abstract: Piperlongumine (PL), a natural alkaloid present in the fruit of the Long pepper, is known to exhibit notable anti-cancer effects. Nonetheless, the anti-tumor effect of PL in lung cancer cells still remains unclear. In the present study, we reported the chemotherapeutic effects of PL using in vitro and in vivo models. We showed that PL displayed potent anti-neoplastic activity against lung cancer A549 cells as well as corresponding docetaxel-resistant A549/DTX cells. In addition, we found that PL induced apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…AKT signalling has an important role in the regulation of cell proliferation, angiogenesis, migration and invasion [48]. Numerous studies revealed that mTOR kinase could suppress autophagy and apoptosis [49]. Our results demonstrated that phosphorylated AKT and phosphorylated mTOR were decreased in both breast cancer cell lines after CEP treatment.…”
Section: Discussionmentioning
confidence: 52%
“…AKT signalling has an important role in the regulation of cell proliferation, angiogenesis, migration and invasion [48]. Numerous studies revealed that mTOR kinase could suppress autophagy and apoptosis [49]. Our results demonstrated that phosphorylated AKT and phosphorylated mTOR were decreased in both breast cancer cell lines after CEP treatment.…”
Section: Discussionmentioning
confidence: 52%
“…PL modulates the activity of many cell signaling and survival pathways in cancer cells [31], and a number of studies have investigated the MOA by which PL induces apoptosis in these cells [30, 3540, 45, 5469]. Data from these studies may be translatable to PL-induced SC apoptosis because SCs and cancer cells share some common pro-survival pathways [23].…”
Section: Discussionmentioning
confidence: 99%
“…AKT can downregulate radiation-induced autophagy and apoptosis in breast cancer cells [32]. The natural alkaloid piperlongumine was shown to activate apoptosis and autophagy in lung cancer cells through inhibition of AKT/mTOR pathway [33]. The antitumor enzyme asparaginase triggers apoptosis and cytoprotective autophagy in chronic myeloid leukemia cells by inhibition of AKT/mTOR signaling pathway [34].…”
Section: Discussionmentioning
confidence: 99%